Growth of Pakcoy (Brassica rapa L.) Hydroponic System Using Nutrients of Catfish Cultivation Waste - Fitra Gustiar; Munandar Munandar; M Amar; Arsi Arsi; Puspa A Pitayati; Tri O Amanah; Nadiya Assyfa (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
Organic hydroponic cultivation systems require substitute nutrients other than inorganic fertilizers as a source of plant nutrients. Catfish cultivation waste is one of the potentials that can be used as hydroponic nutrients. This study aimed to find out the concentration of Liquid Organic Fertilizer (LOF) from fish cultivation waste as a substitute for commercial inorganic nutrients on the growth of pakcoy (Brassica rapa L.). This research was carried out in 2 stages, namely the manufacture of LOF from catfish culture waste and experiments using LOF as hydroponic nutrients. The results of this study showed that the increase in LOF nutrient content in anaerobic fermentation was higher than in aerobic fermentation. The use of LOF as a hydroponic nutrient, based on the parameters of plant height, number of leaves, SPAD value, root weight, crown weight, and dry weight obtained a smaller value that was significantly different compared to the inorganic nutrient treatment of AB mix. LOF concentration of 20%, both fermented aerobically and anaerobically, gave better growth when compared to higher concentration treatments. The nutrient content in LOF is difficult to adjust to the needs of hydroponic pakcoy, so that it will have a toxic impact on macro nutrients on the other hand, it also provides a response to micro nutrient deficiency.